2010
DOI: 10.1177/0148607110362587
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Glutamine Dipeptide–Supplemented Parenteral Nutrition on Outcomes of Surgical Patients

Abstract: GLN-PN was beneficial to postoperative patients by shortening the length of hospital stay and reducing the morbidity of postoperative infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 56 publications
2
33
2
3
Order By: Relevance
“…Implications of such studies would extend beyond malnutrition to encompass other gastrointestinal diseases for which Ala-Gln supplementation has shown some benefit in metanalyses or small clinical studies. These include postsurgical infections (68), acquired immunodeficiency syndrome-associated diarrhea and wasting (7), and chemoradiotherapy mucositis (11).…”
Section: Discussionmentioning
confidence: 99%
“…Implications of such studies would extend beyond malnutrition to encompass other gastrointestinal diseases for which Ala-Gln supplementation has shown some benefit in metanalyses or small clinical studies. These include postsurgical infections (68), acquired immunodeficiency syndrome-associated diarrhea and wasting (7), and chemoradiotherapy mucositis (11).…”
Section: Discussionmentioning
confidence: 99%
“…If a critically ill or surgical patient does acquire an infectious complication, this will prolong that patient's length of stay in hospital and require more resources. Hospital acquired infections are expensive to treat, and it is estimated that hospital acquired infections can prolong a patient's length of stay by at least 4 days; this can have a significant financial impact on hospitalization cost (27). It has been observed that the additional cost of supplemented glutamine treatment is more than completely offset by cost savings in hospital care (37).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent meta-analysis [32]. No data are available with regard to glutamine supplementation for combined enteral and parenteral nutrition.…”
Section: Immunonutritionmentioning
confidence: 97%